Volume 7B: Fluids Engineering Systems and Technologies 2015
DOI: 10.1115/imece2015-51681
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Design Parameters on Aerodynamic Performance of New Profile Small Wind Turbine Blades

Abstract: Wind is a one of the clean resources of energy and has the ability to contribute a considerable share in growing world energy consumption. The small wind turbine plays a vital role in fulfillment of energy needs preferably for household purpose. In order to unleash the budding of applicability of small wind turbine, it is necessary to improve its performance. The performance of a small wind turbine can be distinguished by the manners in which power, thrust and torque vary with the wind speed. The wind power in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…To conclude, the best compromise between the maximum power coefficient, the cut-in wind speed, the mass of filament, and the stability of the wake is achieved for the rotor with a blade solidity of 1.25. Birajdar et al [14] studied the effects of the TSR, angle of attack, rotor solidity, and number of blades on the aerodynamic performance of a small wind turbine. Their results indicated that C P,max was 0.5 at the optimum TSR and angle of attack of 7 and 4.5 • , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…To conclude, the best compromise between the maximum power coefficient, the cut-in wind speed, the mass of filament, and the stability of the wake is achieved for the rotor with a blade solidity of 1.25. Birajdar et al [14] studied the effects of the TSR, angle of attack, rotor solidity, and number of blades on the aerodynamic performance of a small wind turbine. Their results indicated that C P,max was 0.5 at the optimum TSR and angle of attack of 7 and 4.5 • , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…At the end of the 20 th century, with the widespread utilization of small wind turbines, the development of special airfoils for small horizontal-axis wind turbine blades received increasing attention, which greatly stimulated related studies. Representative findings include IND 15045 and IND 09848 airfoils developed by Birajdar, which was designed specifically for 1 kW small horizontal-axis wind turbine [6]. In addition, Singh and Ahmed developed a new airfoil to solve the start-up problem [7].…”
Section: Introductionmentioning
confidence: 99%
“…Power produced by a wind turbine is proportional to the square of rotor diameter and cube of wind velocity. Hence, to obtain, the more power from wind turbine one need to increase either the rotor diameter or wind velocity [1]. Large wind turbine manufacturers are always interested in increasing the rotor diameter to get more power output and achieved satisfactory performance also.…”
Section: Introductionmentioning
confidence: 99%